Bimbingan Konseling Bimbingan Konseling dalam Meningkatkan Atribusi Belajar Siswa-Siswi SMPN 1 Pleret Bantul Yogyakarta - ahmad zulkarnain (JIGC (Journal of Islamic Guidance and Counseling), 2019)
This study aims to see how school counselors (counselors, BK teachers) improve student learning attribution at SMPN 1 Pleret, Bantul. Attribution which is understood as something that exists in a person formed by students then influences the psychological dimension of hope for success, self-efficacy, and affect. And also affect behavior, namely choice, perseverance, and the level of movement of students' efforts in learning. This research is motivated by the majority of students who are not able and have not been able to find something unique in themselves, so that the need for guidance and counseling as a method of understanding students will be important and their personal worth as a person. This research method uses interviews, observations and classroom actions where the researcher is involved in the counseling guidance activities. Counseling guidance model is done in groups, from the group can switch to individual counseling actions. The results showed that counseling guidance in improving student learning attribution at SMPN 1 Pleret Bantul can be said to be good, by meeting the standards of the process of implementing counseling guidance that has been worked out, so as to achieve the desired target.